2009
DOI: 10.1677/joe-08-0432
|View full text |Cite
|
Sign up to set email alerts
|

Dehydroepiandrosterone modifies rat fatty acid composition of serum and different adipose tissue depots and lowers serum insulin levels

Abstract: Dehydroepiandrosterone (DHEA) is reported to exert beneficial effects, such as protection from cardiovascular risk and lowering serum insulin levels. Adipose tissue (AT) is a target for DHEA actions, and the hormone can also affect hepatic fatty acid (FA) metabolism. FAs are involved in the development of insulin resistance; thus, there might be a relationship between DHEA, FA, and insulin. However, few data are available regarding DHEA and FA composition, especially concerning AT. Seventeen-month old female S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
7
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 38 publications
4
7
0
Order By: Relevance
“…d Estimates of delta-5-desaturase activity. Single asterisk represents significant differences at P<0.05 studies regarding AT fatty acid composition performed in rodents showed a similar trend to our observations [16]. Further studies should explore this situation in vivo.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…d Estimates of delta-5-desaturase activity. Single asterisk represents significant differences at P<0.05 studies regarding AT fatty acid composition performed in rodents showed a similar trend to our observations [16]. Further studies should explore this situation in vivo.…”
Section: Discussionsupporting
confidence: 87%
“…More recently, and in the line of the present study, other authors have reported differences in 3T3-L1 adipocytes [25], especially as regards a decrease in palmitic acid. Our own group has formerly shown that DHEA supplementation can modify the AT fatty acid profile of rodents in the same way as the present results shows in humans [16].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In our laboratory, we observed that rats receiving DHEA orally for 13 weeks reproduced some of the changes observed in 3T3-L1 cells. Besides having a significantly lower percentage body fat, DHEA-treated rats had higher proportions of stearic and oleic acids and a lower proportion of palmitoleic acid in their adipose depots [56]. Total n-6 PUFAs were also decreased, while n-3 PUFAs were increased, leading to significant reductions in n-6:n-3 PUFA ratios.…”
Section: Influence Of Sex Hormonesmentioning
confidence: 95%
“…A good example is provided by data showing the effects of dehydroepiandrosterone (DHEA) and its sulfate on experimental animals and humans [55][56][57]. The level of this particular hormone, a precursor of most androgens and estrogens, is strongly related to body fat distribution and also with fatty acid profiles of adipose tissue and plasma.…”
Section: Influence Of Sex Hormonesmentioning
confidence: 99%